2020
DOI: 10.1097/shk.0000000000001683
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Activation of Endogenous GLP-1 System to Gram-negative Sepsis Is Associated With Early Innate Immune Response and Modulated by Diabetes

Abstract: Background: Culture-positive gram-negative sepsis induces greater magnitude of early innate immunity / inflammatory response compared with culture-negative sepsis. We previously demonstrated increased activation of antiinflammatory Glucagon Like Peptide-1 (GLP-1) hormone in initial phase of sepsis more pronounced in diabetes patients. However, whether GLP-1 system is hyperactivated during the early innate immune response to gram-negative sepsis and modulated by diabetes remains unknown. Objectives: Total and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Endogenous glucagon like peptide 1 (GLP‐1) hormone as well as exogenous GLP‐1 analogues are novel anti‐inflammatory immune modulators of the innate immunity response 13,14 . Others and we previously demonstrated significantly increased circulating GLP‐1 levels in non‐surviving patients with sepsis, while persistent elevated levels GLP‐1 after sepsis were found to predict poor long‐term outcome at 6 months 15–17 Moreover, we demonstrated that the hyperactive endogenous GLP‐1 system is closely associated with extreme early innate immune response in patients with severe Gram‐negative sepsis together with sharply increased PCT and lactate and modulated by type 2 diabetes (T2D) 18 …”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Endogenous glucagon like peptide 1 (GLP‐1) hormone as well as exogenous GLP‐1 analogues are novel anti‐inflammatory immune modulators of the innate immunity response 13,14 . Others and we previously demonstrated significantly increased circulating GLP‐1 levels in non‐surviving patients with sepsis, while persistent elevated levels GLP‐1 after sepsis were found to predict poor long‐term outcome at 6 months 15–17 Moreover, we demonstrated that the hyperactive endogenous GLP‐1 system is closely associated with extreme early innate immune response in patients with severe Gram‐negative sepsis together with sharply increased PCT and lactate and modulated by type 2 diabetes (T2D) 18 …”
Section: Introductionmentioning
confidence: 54%
“…[15][16][17] Moreover, severe Gram-negative sepsis is specifically associated with GLP-1 hyperactivation, suggesting that endogenous GLP-1 response during COVID-19 may be upregulated by bacteria-induced systemic inflammation mediated by disrupted intestinal barrier integrity and higher microbial product translocation into the blood. 18,21 It should be noted that SARS-CoV-2 is able to infect not only the respiratory but also the intestinal tract through the ACE2 receptor, and the enteric infection increasing the tight junction permeability and translocation of bacterial products in circulation could probably contribute to the disease progression of COVID-19. [22][23][24] This concept is supported by the reported ability of LPSs to acutely induce GLP-1 secretion in humans and the increased GLP-1 secretion by injured ischaemic human gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that activation of GLP-1 receptors can promote B and T cell expansion, particularly toward Treg1 differentiation, thereby contributing to the impaired inflammatory response in patients with sepsis [ 51 ]. In addition, the massive activation of the endogenous GLP-1 system during sepsis has been proposed as a predictor of early death or persistent organ dysfunction [ 70 , 71 ], particularly in patients infected by Gram-negative bacteria [ 51 , 72 ].…”
Section: Treatment-associated Infectionsmentioning
confidence: 99%
“…On the one hand, its over-activity is related to increased sCD14 levels, which activates the innate immune response to resist the invasion of pathogenic microorganisms. On the other hand, it may reduce excessive inflammation to prevent immune system disorders and the adverse consequences of sepsis ( Bloch et al, 2021 ).…”
Section: Effect Of Glp-1ras On Immune Response Induced By Sepsismentioning
confidence: 99%